"New Citizens" or "Community of Fate"? Early Discourses and Policies on "Flight and Expulsion" in the Two Postwar Germanys. Issue 2 (June 2020) - Gengler, Peter N.
Abstract: The historiography of the postwar Germanys often examined the Nazi legacy and the remarkable efforts needed for economic and social recovery after 1945. In both the FRG and GDR, the consequences of the war and resulting "flight and expulsion" featured prominently in public discourse and were among the most pressing challenges in the early postwar years. Examining how the competing regimes in East and West Germany attempted to solve the humanitarian crisis caused by the forced migration of 10 to 12 million German refugees in the first years after World War II reveals that the discourses and policies started from common points of departure yet diverged into competing narratives underpinning the states' political and social agendas. Reconstructing the evolution of how the forced migrations were discussed and leveraged in the neglected period immediately after the war opens new perspectives on how Germans shouldered the burdens of dictatorship and defeat.